Internet-delivered cognitive therapy for social anxiety disorder in Hong Kong: A randomised controlled trial - Thew, G; Kwok, A; Lissillour Chan, M; Powell, C; Wild, J; Leung, P; Clark, D (Elsevier, 2022)
Background Research is needed to determine the extent to which internet-delivered psychological therapies are effective when delivered in countries and cultures outside of where they were developed.